Slant helices of (k, m)-type in E4 - Yilmaz, Munevver Yildirim; Bektas, Mehmet (De Gruyter Poland Sp Zoo, 2018)
In the present work, we define new type slant helices called (k,m)-type and we conclude that there are no (1,k) type (1 <= k <= 4) slant helices. Also we obtain conditions for different type slant helices.
Keywords: slant helices; Serret-Frenet frame